2021
DOI: 10.3389/fnins.2021.640835
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Autonomic Nervous System Dysfunction in the Early Phase of Infection With SARS-CoV-2 Virus

Abstract: BackgroundWe are facing the outburst of coronavirus disease 2019 (COVID-19) defined as a serious, multisystem, disorder, including various neurological manifestations in its presentation. So far, autonomic dysfunction (AD) has not been reported in patients with COVID-19 infection.AimAssessment of AD in the early phase of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 virus).Patients and methodsWe analyzed 116 PCR positive COVID-19 patients. After the exclusion of 41 patients with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 62 publications
4
87
0
Order By: Relevance
“…The interpretation of V2 related to the parasympathetic activity seems quite probable if one recalls that the parasympathetic branch has the potential to introduce fast (beat to beat) changes in the heart rate, which may even lead to an asystole. The effect of autonomic dysfunction in the early stage of COVID-19 was observed previously in patients with different intensities of symptoms 31 as well as in critical conditions 9 . In the Maartje et al study, the authors discussed the separate roles of the sympathetic branch and vagus nerve in the infection 12 .…”
Section: Discussionsupporting
confidence: 54%
“…The interpretation of V2 related to the parasympathetic activity seems quite probable if one recalls that the parasympathetic branch has the potential to introduce fast (beat to beat) changes in the heart rate, which may even lead to an asystole. The effect of autonomic dysfunction in the early stage of COVID-19 was observed previously in patients with different intensities of symptoms 31 as well as in critical conditions 9 . In the Maartje et al study, the authors discussed the separate roles of the sympathetic branch and vagus nerve in the infection 12 .…”
Section: Discussionsupporting
confidence: 54%
“…Recent studies reported baroreflex dysfunction in the early phase of infection with SARS-CoV-2. 32 Our findings suggest that baroreflex dysfunction could be restored after COVID-19, since BRS was improved during follow-up. Furthermore, BRS and aPWV were inversely correlated in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 52%
“…Noradrenergic neurons in the LC have been associated with a wide array of physiological functions including cardiovascular and respiratory control (de Carvalho et al, 2017; Oyamada et al, 1998) via direct projections to the spinal cord or projections to autonomic nuclei like the dorsal motor nucleus (DMV) of the vagus, the rostroventrolateral medulla (RVM), the Edinger-Westphal nucleus, the caudal raphe, the paraventricular nucleus, and the amygdala (Samuels and Szabadi, 2008). As autonomic functions are impaired in COVID-19 patients after infection (Becker, 2021; Milovanovic et al, 2021) and the LC is one of the regions that is associated with these functions, we tested ACE2 immunoreactivity in LC neurons after CIE exposure. Many TH-positive neurons in the LC were positive for ACE2 expression as previously reported (Hernández et al, 2021) and the number of TH-ACE2 neurons was increased in CIE mice, suggesting an increased vulnerability of LC neurons to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%